Climate change and its implications on wildlife conservation - Priatna, Dolly; Monk, Kathryn Anne (Indonesian Journal of Applied Environmental Studies, 2023)
The Intergovernmental Panel on Climate Change (IPCC) Synthesis Report, released nearly a year ago, summarized five years of reports on global temperature rises, fossil fuel emissions and climate impacts and emphasised that there was “a rapidly closing window of opportunity to secure a liveable and sustainable future for all.”  It demonstrated an undeniable scientific consensus about the urgency of the climate crisis, its primary causes, its current devastating impacts – especially on the most climate vulnerable regions – and the irreversible harm that will occur to both the natural world and human society if warming surpasses 1.5°C, even temporarily. For Indonesia, climate change poses a formidable challenge for its people and its rich terrestrial and marine biodiversity that encompasses such a diverse array of ecosystems ranging from lush rainforests and dry savannas to extensive swamps and coral reefs. As the world's fourth most populous nation and the biggest archipelagic country in the world, Indonesia consists of some 17,000 islands, with over 8,000 km of coastline and is therefore extremely vulnerable to the impacts of global climate change. The nation's rich biodiversity, encompassing iconic species such as the Sumatran tiger, orangutan, and Komodo dragon, is intricately linked to the health of its ecosystems. Rising temperatures, changing precipitation patterns, and the increasing frequency of extreme weather events disrupt these ecosystems, leading to shifts in species composition and distribution.